Schwarschild metric in six dimensions - a topological study - Ahmed, Nasr; Rafat, H. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this article we introduce some types of the deformtion retracts of the 6D Schwarzchild making use of Lagrangian equations. The retraction of this space into itself and into geodesics has been presented. The relation between folding and deformation retract of this space has been achieved. A relation for energy conservation similar to the one obtained in four dimensions has been obtained for the six dimensional case.